The Predict-Observe-Explain Based E-Module on Area and Circumference of Two-Dimentional Shape’s for Fourth Grade Students - Putri Chandranathasya; Sastra Agustika, Gusti Ngurah; Chindytia (Universitas Pendidikan Ganesha, 2025)
This study addresses issues related to mathematics learning, specifically on the topic of the area and perimeter of flat shapes, which can enhance students' understanding and interest in learning mathematics. The purpose of this study is to develop the design and development of a Predict-Observe-Explain (POE) based E-Module product, assess the quality of the E-Module through expert evaluation, individual tests, and small group tests, and determine the effectiveness of the Predict-Observe-Explain-based E-Module media. This research uses the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation), and data collection is carried out through interviews, questionnaires, and tests. The data analysis techniques used are descriptive quantitative analysis and inferential statistics. The results of the study show that the Predict-Observe-Explain based E-Module developed using Canva can be accessed through Google Drive. The assessment from content experts resulted in a score of 97.7%, instructional design experts 90%, and media experts 92.3%. The individual test, involving three students, scored 97.5%, while the small group test, involving nine students, scored 94.4%, both falling in the very good category. The t-test results showed a value of 21.70, which is greater than the t-table value of 2.052 at a 5% significance level with 27 degrees of freedom, thus rejecting H0 and accepting H1, indicating that the average post-test score of students is higher than the average in the KKTP, which is 87.86. Therefore, the Predict-Observe-Explain based E-Module has proven to be effective for teaching the topic of Area and Circumference of Two-Dimentional Shape’ss to fourth-grade students.